Predictors of Health Care Seeking Behavior During Pregnancy, Delivery, and the Postnatal Period in Rural Tanzania. - Larsen, Anna; Exavery, Amon; Phillips, James; Tani, Kassimu; Kanté, Almamy (Maternal & Child Health Journal, 2016)
Objectives Four antenatal visits, delivery in a health facility, and three postnatal visits are the World Health Organization recommendations for women to optimize maternal health outcomes. This study examines maternal compliance with the full recommended maternal health visits in rural Tanzania with the goal of illuminating interventions to reduce inequalities in maternal health. Methods Analysis included 907 women who had given birth within two years preceding a survey of women of reproductive age. Multinomial logistic regression was used to assess the influence of maternal, household, and community-level characteristics on four alternative classes defining relative compliance with optimal configuration of maternal health care seeking behavior. Results Parity, wealth index, timeliness of ANC initiation, nearest health facility type, religion, and district of residence were significant predictors of maternal health care seeking when adjusted for other factors. Multiparous women compared to primiparous were less likely to seek care at the high level [RRR 0.16, 95 % confidence interval (CI) 0.06-0.46], at the mid-level (RRR 0.22, 95 % CI 0.09-0.58), and the mid-low level (RRR 0.27, 95 % CI 0.09-0.80). Women in the highest wealth index compared to those in the poorest group were almost three times more likely to seek the highest two levels of care versus the lowest level (high RRR 2.92, 95 % CI 1.27-6.71, mid-level RRR 2.71, 95 % 1.31-5.62). Conclusion Results suggest that efforts to improve the overall impact of services on the continuum of care in rural Tanzania would derive particular benefit from strategies that improve maternal health coverage among multiparous and low socioeconomic status women.